Inheritance Distribution and Conflict Resolution in Bone Regency: Upholding Women's Rights and Islamic Law Objectives - Tarmizi, Tarmizi; Amir, Rahma; Syamsuddin, Darussalam; Hasan, Hamzah; Ridwan, Muh. Saleh (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2024)
The implementation of the inheritance distribution system within the community remains partially ineffective, as conflicts among heirs frequently arise. These disputes hinder the objectives of Islamic law as outlined in maqāṣid al-syarīʿah, emphasizing the need for preventive efforts. This study aims to analyze inheritance conflict prevention in Bone Regency through gender-equitable deliberation by examining conflict resolution methods, causes of disputes, women’s inheritance rights, and conflict prevention strategies from the perspective of maqāṣid al-syarīʿah. This empirical research was conducted in Bone Regency using a theological-normative approach based on maqāṣid al-syarīʿah. Primary data were collected through interviews with academics, judges, and government officials, while secondary data were obtained from relevant literature and analyzed qualitatively. The findings reveal that inheritance disputes can be resolved through court litigation or non-litigation pathways involving local authorities. Key causes of conflicts include heirs’ greed, limited understanding of inheritance laws, lack of property transfer documentation, unfair distribution, and delays in inheritance division. Women's inheritance rights in Bone's customary law are preserved through deliberation during the distribution process. To prevent inheritance disputes, measures such as public education on inheritance law, facilitated consultations involving local authorities, and proper documentation of property transfers are recommended. These initiatives align with the values of maqāṣid al-syarīʿah, which prioritize the preservation of religion, life, intellect, property, and lineage. The government and relevant stakeholders are expected to play an active role in guiding and educating communities to ensure effective inheritance distribution and prevent conflicts.